Theories of coalitional rationality - Attila Ambrus (Hungarian Academy of Sciences, Institute of Economics, 2005)
This paper generalizes the concept of best response to coalitions of players and offers epistemic definitions of coalitional rationalizability in normal form games. The best response of a coalition is defined to be a correspondence from sets of conjectures to sets of strategies. From every best response correspondence it is possible to obtain a definition of the event that a coalition is rational. It requires that if it is common certainty among players in the coalition that play is in some subset of the strategy space then they confine their play to the best response set to those conjectures. A strategy is epistemic coalitionally rationalizable if it is consistent with rationality and common certainty that every coalition is rational. A characterization of this set of strategies is provided for best response correspondences that satisfy four properties: monotonicity, a weak form of Pareto-optimality and two consistency requirements with individual best responses. Special attention is devoted to a correspondence that leads to a solution concept that is generically equivalent to the iteratively defined concept of coalitional rationalizability (Ambrus [04]).
Keywords: 330; noncooperative games; coalition agreements; rationalizability; epistemic solution concept